Hubungan Personal Hygiene dan Tingkat Pengetahuan dengan Kejadian Skabies pada Santri Pesantren Miftahul Huda Al-Hadi Tasikmalaya - Shafira Nefananda Kariza; Herry Garna; Agung Firmansyah Sumantri (Bandung Conference Series: Medical Science, 2022)
Abstract. Scabies is an infectious skin disease due to the infestation and sensitization of the mite Sarcoptes scabiei (S. scabiei) which is a parasite that can tunnel through the skin. Scabies is often in inhabited places such as boarding schools, dormitories, prisons, and areas, occurring in association with poor hygiene and behavior. The purpose of this study was to determine the relationship between personal hygiene and knowledge level with the incidence of scabies in male students at Miftahul Huda Al-Hadi Islamic Boarding School Tasikmalaya. This study used an observational method with a cross-sectional design using a questionnaire and related patient data forms. The number of respondents in this study amounted to 65 people who were taken using purposive sampling. Data collection was carried out in the period March–October 2021. The results showed that the majority of students at Miftahul Huda Al-Hadi Islamic Boarding School Tasikmalaya 40 students (62%) experienced scabies. The majority of students' hygiene was sufficient (51%) and the level of knowledge was poor (65%). The results of the bivariate chi-square analysis showed that there was a relationship between personal hygiene and level of knowledge with the incidence of scabies (p-value = 0.001 > 0.05). In conclusion that there is a relationship between personal hygiene and level of knowledge with the incidence of scabies in students at Miftahul Huda Al-Hadi Islamic Boarding School Tasikmalaya. Abstrak. Skabies adalah penyakit kulit menular yang disebabkan oleh infeksi tungau (S. scabiei), parasit yang dapat menyerang kulit. Skabies sering terjadi di tempat berpenghuni banyak seperti pondok pesantren, asrama, penjara, dan daerah kumuh, yang berhubungan dengan kebersihan dan perilaku penghuni yang buruk. Tujuan penelitian ini adalah memperjelas hubungan personal hygiene dan tingkat pengetahuan dengan kejadian skabies pada santri di Pondok Pesantren Miftahul huda Al Hadi Tasikmalaya. Penelitian ini adalah metode observasional dengan rancangan cross sectional menggunakan kuesioner dan formulir data santri terkait. Responden penelitian ini berjumlah 65 orang yang diambil dengan teknik purposive sampling. Pengambilan data dilakukan periode bulan Maret hingga Oktober 2021. Hasil penelitian menunjukkan mayoritas santri di Pondok Pesantren Miftahul Huda Al-Hadi Tasikmalaya 40 orang santri (62%) mengalami kejadian skabies. Mayoritas personal hygiene santri cukup (51%) dan tingkat pengetahuan buruk (65%). Hasil analisis bivariat chi-square menunjukkan hubungan personal hygiene dan tingkat pengetahuan dengan kejadian skabies (p = 0,001 > 0,05). Simpulan, terdapat hubungan personal hygiene dan tingkat pengetahuan dengan kejadian skabies pada santri di Pondok Pesantren Miftahul Huda Al-Hadi Tasikmalaya.